Control and Prevention of the COVID-19 Epidemic in China: A Qualitative Community Case Study - Wu Y; Zhang Q; Li L; Li M; Zuo Y (Dove Medical Press, 2021)
Yijin Wu,1 Quan Zhang,2,3 Linzi Li,4 Meiyu Li,5 Ying Zuo2 1School of Translation Studies, Qufu Normal University, Rizhao, Shandong, People's Republic of China; 2School of International Affairs and Public Administration, Ocean University of China, Qingdao, Shandong, People's Republic of China; 3Centre for Quality of Life and Public Policy, Shandong University, Qingdao, Shandong, People's Republic of China; 4Rizhao Maternal and Child Health Hospital, Rizhao, Shandong, People's Republic of China; 5School of Economics and Management, China University of Petroleum (East China), Qingdao, Shandong, People's Republic of ChinaCorrespondence: Quan Zhang Email waltawhite@163.comBackground: Cross-infection among residents in communities is one of the most critical reasons for the rapid spread of the COVID-19 epidemic. The COVID-19 epidemic has been well controlled within Chinese communities, which has made important contributions to the country's fight against it.Methods: In this study, a qualitative case study design, with mixed methods applied to data collection and analysis, was employed to explore epidemic prevention measures taken by a Chinese community, namely Mulin, during the pandemic.Results: The Mulin community established an integrated plan for epidemic prevention, including the prevention of the invasion of COVID-19, the prevention of cross-infection within the community, gaining the residents' trust and support, and providing the residents with convenient services.Conclusion: In the present work, the Mulin community was taken as a typical case study, and qualitative methods were employed to comprehensively summarize the practice and experience of the community's epidemic prevention. Mulin's practices could shed light on how communities in other countries, especially developing countries with large populations, can prevent the spread of COVID-19.Keywords: COVID-19, epidemic prevention, community, China